Evaluating parental experiences in teaching children with learning disabilities in resource rooms of public schools in Amman - Alramamneh, Abdellatif Khalaf; Al-Sabayleh, Obaid Abdelkarim; Alsarayreh, Khaled Shaker Turki; Al Remawi, Sameer Abdel Kareem Ahmad (Frontiers in Education, 2024)
Background: The education of children with learning disabilities in public schools' resource rooms remains a vital area of concern, particularly in Amman, where diverse educational needs and varying levels of resource allocation pose significant challenges. . Aim: This study aimed to address this gap by evaluating the perspectives of parents of students with learning disabilities in resource rooms within Amman's public schools, focusing on their satisfaction with educational services, including instruction quality, resource adequacy, and facility accessibility. A cross-sectional study design was utilized, involving a structured questionnaire administered to 200 parents of children attending resource rooms in 33 public schools across Amman. Data were analyzed using SPSS version 27 to compute descriptive statistics, correlation coefficients, and hierarchical linear modeling (HLM) to account for clustering effects. The majority of respondents were female (60%, n = 120), and the largest age group was 31-40 years (45%, n = 90). Most parents held a Bachelor's degree (50%, n = 100) and were employed (75%, n = 150). The predominant age group of the children was 11-15 years (50%, n = 100), with dyslexia being the most common type of learning disability (40%, n = 80). Parents rated the quality of instruction at a mean of 3.5 (SD = 1.2), adequacy of educational materials at 3.3 (SD = 1.1), and overall satisfaction with the program at 3.6 (SD = 1.0). Accessibility of facilities was rated lower at 2.8 (SD = 1.3). This interpretation is based on the lower mean score, which indicates a less favorable perception of accessibility, and the relatively high standard deviation, which reflects variability in parental experiences. HLM analysis revealed significant positive relationships between quality of instruction (β = 0.75, SE = 0.05, t = 15.00, p < 0.01), adequacy of educational materials (β = 0.70, SE = 0.04, t = 17.50, p < 0.01), and accessibility of facilities (β = 0.65, SE = 0.06, t = 10.83, p < 0.01) with overall parental satisfaction. The study underscores the importance of high-quality instruction, sufficient educational materials, and improved facility accessibility in enhancing parental satisfaction with resource room programs in Amman.